2015
DOI: 10.1155/2015/968087
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterials for Pelvic Floor Reconstructive Surgery: How Can We Do Better?

Abstract: Stress urinary incontinence (SUI) and pelvic organ prolapse (POP) are major health issues that detrimentally impact the quality of life of millions of women worldwide. Surgical repair is an effective and durable treatment for both conditions. Over the past two decades there has been a trend to enforce or reinforce repairs with synthetic and biological materials. The determinants of surgical outcome are many, encompassing the physical and mechanical properties of the material used, and individual immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 99 publications
(233 reference statements)
0
71
0
Order By: Relevance
“…Biologically derived materials are classed as acellular collagen matrices and are often derived from the dermis, pericardium, small intestinal submucosa or urinary bladder matrix of bovine or porcine origin [1, 22, 59]. These materials can undergo crosslinking, the formation of excessive intra- and inter-molecular bonds, to improve the longevity of the material [59].…”
Section: Materials Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biologically derived materials are classed as acellular collagen matrices and are often derived from the dermis, pericardium, small intestinal submucosa or urinary bladder matrix of bovine or porcine origin [1, 22, 59]. These materials can undergo crosslinking, the formation of excessive intra- and inter-molecular bonds, to improve the longevity of the material [59].…”
Section: Materials Discussionmentioning
confidence: 99%
“…The distinction between applications is important because reported complication rates differ significantly for these two device types [1, 15]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the PPM is one of the most used meshes in clinics for pelvic floor reconstruction. 4 Falagas et al 23 reported an infection rate of 0%-8% and an erosion rate of 0%-33% with PPM, problems which have not been overcome. 23 Because biological meshes have the advantage of being biocompatible and tissue inductive, more and more surgeons and researchers have become interested in the biological meshes for pelvic floor reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, the limitations of biologically derived mesh include the size of materials, potentially viral or prion transmission, and relatively low mechanical strength. 4 The mechanical strength of biological meshes can be enhanced with cross-linking processes, but many animal studies have shown that cross-linking has a negative effect on the degradation profile and host response to the materials. [5][6][7] Currently, there is no consensus on the optimal material for POP repair.…”
Section: Introductionmentioning
confidence: 99%